Naturally occuring compounds from glycosmis species (rutaceae) and their biological activity - Rahmani, Mawardi (2005)
Detailed isolation and structural elucidation works on six Glycosmis species, G. calcicola, G. rupestris, G. crassifolia, G. chlorosperma, G. elongate and G. cochinensis have to led to the identification of different classes of compounds including alkaloids, coumarins, flavones, sulphones, triterpenes etc. Some ectracts and pure compounds of Glycosmis species were found to be strongly active when tested against various bioassay plates and spraying the plates with spore suspension of indicator fungus prepared from Aspergillus flavus. The major contributor to this activity were due to the presence of flindersine and desmethoxyzanthophiline. The structures of the isolated compounds were determined by spectroscopic method. Glycosmis species is one of the very few plant species known to contain sulphur-containing compounds. A sulphone, methylgerambullin, isolated from the same plant exhibited only mild antifungal activity but gave excellent results when tested on a series of cancer cell lines. The IC50 values obtained were 0.25, 1.2, 1.5 and 1.7 µg/ml against CEM-SS, KU812F,HT29 and UACC cell lines, respectively. The CHCI₃ extracts of both G. chlorosperma and G. cochchichinensis also exhibited strong activity against T-lymphoblastic cell line (CEM-SS) with IC₅₀ values of 1.5 and 0.75 µg/ml due to the presence of other sulphones.